2019
DOI: 10.3390/s19225022
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Signatures of X-ray Scatter Using Energy-Resolving Photon-Counting Detectors

Abstract: Energy-resolving photon-counting detectors (PCDs) separate photons from a polychromatic X-ray source into a number of separate energy bins. This spectral information from PCDs would allow advancements in X-ray imaging, such as improving image contrast, quantitative imaging, and material identification and characterization. However, aspects like detector spectral distortions and scattered photons from the object can impede these advantages if left unaccounted for. Scattered X-ray photons act as noise in an imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…The attenuation coefficient of the low-Z background reduces as the energy increases, meaning µ b (E 1 ) > µ b (E 2 ). Similarly, our previous work [17] has shown that the scatter fraction reduces as the energy increases, meaning SF (E 1 ) > SF (E 2 ). However, it can be determined that the underestimation due to the µ b (E 1 ) and SF (E 2 ) term has a larger impact than the overestimation due to the µ b (E 2 ) and SF (E 1 ) term.…”
Section: B Impact Of Scattered Radiation In Dessupporting
confidence: 72%
See 3 more Smart Citations
“…The attenuation coefficient of the low-Z background reduces as the energy increases, meaning µ b (E 1 ) > µ b (E 2 ). Similarly, our previous work [17] has shown that the scatter fraction reduces as the energy increases, meaning SF (E 1 ) > SF (E 2 ). However, it can be determined that the underestimation due to the µ b (E 1 ) and SF (E 2 ) term has a larger impact than the overestimation due to the µ b (E 2 ) and SF (E 1 ) term.…”
Section: B Impact Of Scattered Radiation In Dessupporting
confidence: 72%
“…Rather, this method relies on physically modeling the scatter interactions and an off-line scatter database of homogeneous PMMA slabs. Unlike [40] who prepared the database through beam-stop array, we used Monte Carlo simulation to accurately account for the spectrally-varying scatter fractions [17]. Although we considered constant thickness objects (as relevant to the breast compression in clinical mammography), this method may be expanded to prepare a scatter database of non-uniform thickness objects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various types of sensors and detectors exist. In the X-ray range, examples include ionization chambers (gas discharge counters) [1,2], scintillation counters (chambers) [3] in which X-ray radiation is converted into visible light, or solid-state detectors [4][5][6][7], in which X-ray photons generate electron-hole pairs and the corresponding current is recorded. Improvement of existing detector types or the creation of new detectors (using new physical principles) equates to progress in sensing.…”
Section: Introductionmentioning
confidence: 99%